2022
DOI: 10.1007/s00167-022-06942-3
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular injection receipt within 3 months prior to primary total knee arthroplasty is associated with increased periprosthetic joint infection risk

Abstract: PurposeThis systematic review and meta‐analysis analyzed the influence of pre‐operative intra‐articular injections (IAI) on periprosthetic joint infection (PJI) rates after primary total knee arthroplasty (TKA). MethodsStudies published between January 1st, 2000 and May 1st, 2021 evaluating PJI rates among TKA patients with and without IAI were identified from PubMed, Cochrane Library, MEDLINE, EBSCO Host, and Google Scholar. The pooled effect of IAI on PJI risk was calculated utilizing Mantel–Haenszel (M–H) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 42 publications
0
11
1
Order By: Relevance
“…Richardson et al 32 reported that the risk of PJI was significantly greater when intraarticular corticosteroid injection was given within 3 mo (odds ratio=1.21, P =0.014), but not within 6 mo (odds ratio=1.07, P =0.414) or 12 mo (odds ratio=1.17, P =0.081) of TKA. Avila et al 33 confirmed those findings in a metaanalysis of 12 studies with 40,979 patients undergoing TKA within 3 mo after prior IAI. The odds ratio for that group (1.23) was significant ( P <0.0001) when compared with the control group.…”
Section: Literature Reviewmentioning
confidence: 62%
See 1 more Smart Citation
“…Richardson et al 32 reported that the risk of PJI was significantly greater when intraarticular corticosteroid injection was given within 3 mo (odds ratio=1.21, P =0.014), but not within 6 mo (odds ratio=1.07, P =0.414) or 12 mo (odds ratio=1.17, P =0.081) of TKA. Avila et al 33 confirmed those findings in a metaanalysis of 12 studies with 40,979 patients undergoing TKA within 3 mo after prior IAI. The odds ratio for that group (1.23) was significant ( P <0.0001) when compared with the control group.…”
Section: Literature Reviewmentioning
confidence: 62%
“…Multiple studies have reported a similar temporal relationship between postoperative infection and IAI in patients undergoing TKA. 32,33 Specifically, an increased infection risk has been reported when IAI was given within 3 mo before TKA. Richardson et al 32 reported that the risk of PJI was significantly greater when intraarticular corticosteroid injection was given within 3 mo (odds ratio = 1.21, P = 0.014), but not within 6 mo (odds ratio = 1.07, P = 0.414) or 12 mo (odds ratio = 1.17, Current Orthopaedic Practice www.c-orthopaedicpractice.com | 67…”
Section: Newer Evidencementioning
confidence: 99%
“…A large database study by Cancienne et al, however, had a limitation in that the database was confined to a Medicare-only population [ 15 ], making it difficult to apply their results to the younger population [ 4 ]. Recent meta-analyses did not distinguish injected medications in assessing the risk of PJI [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies included patients who underwent knee joint arthroplasty and patients who underwent hip joint arthroplasty together in assessing the risk of PJI [ 20 22 ]. Some authors did not specify medications injected into the joint (corticosteroid, hyaluronic acid, or others) [ 23 , 24 ]. The previous studies have investigated the risk of PJI in the setting of various time intervals (from 4 weeks to 1 year) between preoperative injections and arthroplasty [ 25 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kurz et al determined that intra-articular injections of hyaluronic acid or corticosteroid given within the 4-month period before TKA were not related to a high PJI risk within the elderly Medicare patient population [ 60 ]. According to Avila et al, individuals receiving intra-articular injections should wait at least 3 months prior to experiencing TKA to lessen infection risk [ 61 ]. Yang et al reported that intra-articular injections of corticosteroid or hyaluronic acid prior to TKA increased the risk of postoperative infection.…”
Section: Discussionmentioning
confidence: 99%